2020
DOI: 10.3390/s20185388
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Pre-Impact Falls from Heights Using an Inertial Measurement Unit Sensor

Abstract: Many safety accidents can occur in industrial sites. Among them, falls from heights (FFHs) are the most frequent accidents and have the highest fatality rate. Therefore, some existing studies have developed personal wearable airbags to mitigate the damage caused by FFHs. To utilize these airbags effectively, it is essential to detect FFHs before collision with the floor. In this study, an inertial measurement unit (IMU) sensor attached to the seventh thoracic vertebrae (T7) was used to develop an FFH detection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…For safety reasons, a dummy (Madamade, Chuncheon, Gangwon-do, Korea) (height: 180 cm, weight: 10 kg) was used for the HF experiments with fall heights higher than 2 m. Vertical and forward falling movements (FFH) were performed by the dummy at heights of 2 m and 3 m. All movements were repeated five times. Our previous study [15] revealed no differences between the data obtained when a person fell forward from 0.7 m and when a dummy fell forward from the same height using an SPSS-based independent sample t-test.…”
Section: Methodsmentioning
confidence: 84%
See 2 more Smart Citations
“…For safety reasons, a dummy (Madamade, Chuncheon, Gangwon-do, Korea) (height: 180 cm, weight: 10 kg) was used for the HF experiments with fall heights higher than 2 m. Vertical and forward falling movements (FFH) were performed by the dummy at heights of 2 m and 3 m. All movements were repeated five times. Our previous study [15] revealed no differences between the data obtained when a person fell forward from 0.7 m and when a dummy fell forward from the same height using an SPSS-based independent sample t-test.…”
Section: Methodsmentioning
confidence: 84%
“…Several studies have been conducted on developing FFH detection algorithms by extending the aforementioned research [2,14,15]. Yang, et al [2] performed near-miss fall detection based on machine learning with IMU sensor data, where the algorithm showed 86.8% accuracy in the laboratory and 85.2% accuracy outdoors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, three different types of algorithms for pre-impact fall detection were implemented based on this comprehensive motion dataset. All of them were adopted from the state-ofthe-art algorithms published recently (Jung et al, 2020;Kim et al, 2020;Yu et al, 2020Yu et al, , 2021 and thus were representative to be the benchmarks. It was expected that the thresholdbased algorithm showed poorer performance compared with machine learning algorithms (SVM and ConvLSTM) since the number of motion features considered for the threshold-based algorithm was much less than the other two algorithms.…”
Section: Discussionmentioning
confidence: 99%
“…For the threshold-based algorithm, four thresholds (magnitude of acceleration, pitch angle, roll angle, and vertical velocity) were considered to detect a pre-impact fall based on recent publications (Jung et al, 2020;Kim et al, 2020). The magnitude of the acceleration is the L-2 norm of acceleration readings from three axes.…”
Section: Benchmark Algorithms For Pre-impact Fall Detectionmentioning
confidence: 99%